Maximizing the impact of HIV prevention efforts: Interventions for couples - Medley, Amy (AIDS Care, 2013)
Despite efforts to increase access to HIV testing and counseling services, population coverage remains low. As a result, many people in sub-Saharan Africa do not know their own HIV status or the status of their sex partner(s). Recent evidence, however, indicates that as many as half of HIV-positive individuals in ongoing sexual relationships have an HIV-negative partner and that a significant proportion of new HIV infections in generalized epidemics occur within serodiscordant couples. Integrating couples HIV testing and counseling (CHTC) into routine clinic- and community-based services can significantly increase the number of couples where the status of both partners is known. Offering couples a set of evidence-based interventions once their HIV status has been determined can significantly reduce HIV incidence within couples and if implemented with sufficient scale and coverage, potentially reduce population-level HIV incidence as well. This article describes these interventions and their potential benefits.